(3GdJUajI ddbdhH YfO cOQ GdChRGQ hGdPfhHs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s ((3eMeO Hf Ydi Hf GdMGL GdeSjHi s)
(3ChdgG (B:s
(3GdMeO ddg GdeHOY GddWja GdNHjQ CeGHYO , aEf GdebUhO HgPG GdEedGA gi GdETGQI Zdi JUajI GdfahS Yf GdQPGFd , hJRcjI GdCNdGb hGdJMdi HeMGSf GdTeGFd , hJWgjQgG Yf GdChUGa GdQOjI s
(3BNQgG (B:s
(3hdfNJe cJGHfG gPG HGdEHJgGd Edi Gddg , hGdEYJPGQ Edjg , afbhd (B: (3Gddge EfG fSJZaQc ef LejY eG gLS ai GdCaFOI hGdNhGWQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdYfhGfGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeYi GdcHjQ GdZQHjI (B((3JUha (B11) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs